Análise dos pregões eletrônicos realizados em universidades federais localizadas no Rio Grande do Sul - Gomes, Thiago Eliandro de Oliveira (2017)
Public management plays a fundamental role in stimulating economic development and reducing social inequality that mark the country. Inserted in an environment of approximation between society and public management, the university, in solidarity with the administration, has the role of contributing to the aspects of promoting change and of being a development inducer, based on the pillars of teaching, research and extension. However, meeting the demands of the company's interests requires the application of public resources to cover the acquisition of materials and contracting services of many types. Under a position of zeal for public spending, government procurement is subject to the Bidding Law, which culminates in the performance of public management in assuming specific and standardized procedures directed to a negotiation aimed at reducing the estimated price. The objective of this research was to investigate the existing relationships between the variables that impact on the price of the electronic trading floor in three Federal Universities located in Rio Grande do Sul. The monthly percentage variations between the estimated and final price, the number of bidders that offered bids and the number of trading sessions carried out from 2011 to 2016. Descriptive statistics were used for the analyzes in order to outline and describe their characteristics. Subsequently, a study was conducted exploring the relationships between the monthly percentage changes and the number of bidders and, subsequently, the regression models were adjusted to analyze the time evolution, respectively, for the number of bidders and the number of trading sessions institutions of the study. It was found that 73.68% were trades made for acquisition of materials for the institutions, and the other 26.32% related to the contracting of services and that the number of bidding companies was over 90 thousand. It was observed that there was a significant, although weak, correlation between the variables, in the case of UFRGS, for medium and large companies, and in UFSM and UNIPAMPA, for the number of small bidders in the hiring of services. The adjustment of the linear regression models to the number of bidders was statistically significant and, for the most part, the angular coefficients were negative. In addition, it was observed, through the parallelism between the lines, indicating similar growth between the IFES in the number of trading sessions. It was concluded that in the period, the electronic trading sessions brought more than R $ 1.5 billion of savings to the institutions studied and that there was an inverse correlation between the percentage variations and the number of bidders who offered bids during the electronic trading sessions, in most IFES, there was a decrease in the number of bidders during the period considered.